Predictors of cardiac involvement in idiopathic inflammatory myopathies - Bandeira, Matilde; Dourado, Eduardo; Melo, Ana Teresa; Martins, Patrícia; Fraga, Vanessa; Ferraro, José Luís; Saraiva, André; Sousa, Marlene; Parente, Hugo; Soares, Catarina; Correia, Ana Margarida; Almeida, Diogo Esperança; et al. (Frontiers in Immunology, 2023)
Objectives: Idiopathic inflammatory myopathies (IIM) are a group of rare disorders that can affect the heart. This work aimed to find predictors of cardiac involvement in IIM. Methods: Multicenter, open cohort study, including patients registered in the IIM module of the Rheumatic Diseases Portuguese Register (Reuma.pt/Myositis) until January 2022. Patients without cardiac involvement information were excluded. Myo(peri)carditis, dilated cardiomyopathy, conduction abnormalities, and/or premature coronary artery disease were considered. Results: 230 patients were included, 163 (70.9%) of whom were females. Thirteen patients (5.7%) had cardiac involvement. Compared with IIM patients without cardiac involvement, these patients had a lower bilateral manual muscle testing score (MMT) at the peak of muscle weakness [108.0±55.0 vs 147.5±22.0, p=0.008] and more frequently had oesophageal [6/12 (50.0%) vs 33/207 (15.9%), p=0.009] and lung [10/13 (76.9%) vs 68/216 (31.5%), p=0.001] involvements. Anti-SRP antibodies were more commonly identified in patients with cardiac involvement [3/11 (27.3%) vs 9/174 (5.2%), p=0.026]. In the multivariate analysis, positivity for anti-SRP antibodies (OR 104.3, 95% CI: 2.5-4277.8, p=0.014) was a predictor of cardiac involvement, regardless of sex, ethnicity, age at diagnosis, and lung involvement. Sensitivity analysis confirmed these results. Conclusion: Anti-SRP antibodies were predictors of cardiac involvement in our cohort of IIM patients, irrespective of demographical characteristics and lung involvement. We suggest considering frequent screening for heart involvement in anti-SRP-positive IIM patients.